DIFFERENT TYPES OF HEADACH IN PATIENTS PRESENTING TO OUTPATIENT DEPARTMENT AT PAK EMIRATES MILITARY HOSPITAL, RAWALPINDI (The Research of Medical Science Review, 2025)
Background: Headache disorders are among the leading causes of global neurological disability. However, clinical epidemiological data from Pakistan remain scarce, particularly regarding diagnostic patterns and comorbid profiles. Objectives: This study aimed to characterize the spectrum of primary headache disorders using the International Classification of Headache Disorders, 3rd edition (ICHD-3) criteria, in patients presenting to the Neurology Outpatient Department at Pak Emirates Military Hospital (PEMH), Rawalpindi. Methods: This prospective observational study was conducted between July 2024 and April 2025, enrolling 250 adult patients presenting with primary headache complaints. Patients with secondary headaches due to trauma, infections, or intracranial pathology were excluded. Data were collected through structured interviews conducted by trained neurologists and supplemented by medical record reviews. Variables included demographic characteristics, headache type and frequency, triggers, associated symptoms, comorbidities, and diagnostic history. Results: Migraine was the most prevalent diagnosis (68.4%, n = 171), followed by tension-type headache (TTH, 24.8%, n = 62), medication-overuse headache (MOH, 4.4%, n = 11), and cluster headache (2.4%, n = 6). The cohort had a female predominance (72.8%) and a median age of 34 years (IQR: 25–49). Chronic daily headache (≥15 days/month) affected 28.8% of patients, with 64% being migraineurs. Menstruation was a major trigger among female migraineurs (95%), and migraine attacks were more likely to last >24 hours and be associated with photophobia (82.5%), nausea (76.6%), and vomiting (44.4%). Comorbidities included obesity (31.6%), hypertension (22.4%), and depression (18.8%), with obesity correlating positively with headache frequency (r = 0.24, p = 0.01). Misdiagnosis occurred in 14.8% of cases, primarily as sinusitis or temporomandibular joint disorders. Conclusion: Migraine is the predominant primary headache disorder in Pakistani clinical cohort. The study highlights diagnostic challenges, high chronicity rates and significant comorbidities, emphasizing the need for improved adherence to ICHD-3 criteria and multidisciplinary headache management approaches.